Bridging borders: Global insights and challenges in internationalising higher education using a decade-long case study - Mbachi Ruth Msomphora (International Journal of Educational Research Open, 2025)
The manuscript examines a decade of internationalisation efforts at the Department of Health and Care Sciences at UiT The Arctic University of Norway. Employing a mixed-methods approach, it analyses student mobility, research collaborations, and international partnerships, offering strategic recommendations to enhance global educational practices. The findings provide valuable insights into international education, with applications in research, policy, and practice beyond the study's context. Challenges such as the COVID-19 pandemic and financial constraints are highlighted, along with the need for cultural competence and adaptive strategic planning. The study proposes solutions, including flexible exchange programs, the use of virtual technologies, and increased international collaboration to advance higher education in a globalised world.